EPISTEMOLOGICAL ASPECTS OF THE CONCEPT OF CARE/COMFORT: THE OBJECT OF WORK AND THE OBJECT OF NURSING KNOWLEDGE - Carlos Roberto Lyra da Silva; Vilma de Carvalho; Nébia Maria Almeida de Figueiredo; Teresa Tonini (Universidade Federal do Paraná, 2011)
Reflection on epistemological aspects of care and comfort as objects of knowledge in Nursing. The study emphasizes the importance of specificity of objects of knowledge in relation to coherence in epistemological thinking about nursing care and comfort. These objects appear in the space of exteriority - at the edge of - scientific knowledge and thinking. However, the care may have been wished for recently in other areas of knowledge and inserted in imaginary collectives, in the rules of logical thinking, and in discursive formations, capable of linking values and knowledge with thinking and reason in the training of nurses who care or investigate.